Carbon availability affects already large species-specific differences in chemical composition of ectomycorrhizal fungal mycelia in pure culture - Fransson, Petra; Robertson, A. H. Jean; Campbell, Colin D. (Mycorrhiza, 2023)
Although ectomycorrhizal (ECM) contribution to soil organic matter processes receives increased attention, little is known about fundamental differences in chemical composition among species, and how that may be affected by carbon (C) availability. Here, we study how 16 species (incl. 19 isolates) grown in pure culture at three different C:N ratios (10:1, 20:1, and 40:1) vary in chemical structure, using Fourier transform infrared (FTIR) spectroscopy. We hypothesized that C availability impacts directly on chemical composition, expecting increased C availability to lead to more carbohydrates and less proteins in the mycelia. There were strong and significant effects of ECM species ( R 2 = 0.873 and P = 0.001) and large species-specific differences in chemical composition. Chemical composition also changed significantly with C availability, and increased C led to more polysaccharides and less proteins for many species, but not all. Understanding how chemical composition change with altered C availability is a first step towards understanding their role in organic matter accumulation and decomposition.